Female sexuality in times of the COVID-19 pandemic (Research, Society and Development, 2021)
Objective: To clarify possible elements that influence female sexual quality and autonomy during the COVID-19 pandemic. Methods: Integrative review based on the leading question: “How is the situation of female sexuality during the COVID-19 pandemic?”. Searches were performed in the online databases Virtual Health Library (BVS) and Scientific Electronic Library Online (SciELO). Articles available in Portuguese, between the years 2017 to 2021 and that addressed the studied topic were included, excluding those that were not related to the proposed topic and did not present the full text available. After the analysis process, 18 publications were selected to compose the discussion and presentation of this review. Results: There is a lack of available works on the subject, considering that is a current theme. The pandemic in 2019, developed changes in behavior, coexistence, self-knowledge, sexual practice and reproduction. This global context exposed the problem that the guidelines of the SUS cannot be carried out in excellence, causing a dangerous deficit of information. Final considerations: It is important to establish effective means of encouraging female empowerment and a health care system that takes into consideration the socioeconomic and cultural situation of the women.